Erratum to: Measurement of the CKM angle γ using B ± → DK ± with D → K S 0 π + π −, K S 0 K + K − decays - The LHCb collaboration; R. Aaij; B. Adeva; M. Adinolfi; C. A. Aidala; Z. Ajaltouni; S. Akar; P. Albicocco; J. Albrecht; F. Alessio; M. Alexander; A. Alfonso Albero; et al. (Journal of High Energy Physics, 2018)
The B + and B − labels of the confidence regions in figure 10 of the original paper [1] were erroneously swapped. The corrected figure is shown in figure 10.